Copper determination in ethanol fuel by differential pulse anodic stripping voltammetry at a solid paraffin-based carbon paste electrode modified with 2-aminothiazole organofunctionalized silica - Takeuchi, Regina M.; Santos, Andre L.; Padilha, Pedro M.; Stradiotto, Nelson Ramos [UNESP] (Elsevier B.V., 2007)
Solid paraffin-based carbon paste electrodes modified with 2-aminothiazole organofunctionalized silica have been applied to the anodic stripping determination of copper ions in ethanol fuel samples without any sample treatment. The proposed method comprised four steps: (1) copper ions preconcentration at open circuit potential directly in the ethanol fuel sample; (2) exchange of the solution and immediate cathodic reduction of the absorbate at controlled potential; (3) differential pulse anodic stripping voltammetry; (4) electrochemical surface regeneration by applying a positive potential in acid media. Factors affecting the preconcentration, reduction and stripping steps were investigated and the optimum conditions were employed to develop the analytical procedure. Using a preconcentration time of 20 min and reduction time of 120 s at -0.3 V versus Ag/AgCl(sat) a linear range from 7.5 x 10(-8) to 2.5 x 10(-6) mol L(-1) with detection limit of 3.1 x 10(-8) mol L(-1) was obtained. Interference studies have shown a decrease in the interference effect according to the sequence: Ni > Zn > Cd > Pb > Fe. However, the interference effects of these ions have not forbidden the application of the proposed method. Recovery values between 98.8 and 102.3% were obtained for synthetic samples spiked with known amounts of Cu(2+) and interfering metallic ions. The developed electrode was successfully applied to the determination of Cu(2+) in commercial ethanol fuel samples. The results were compared to those obtained by flame atomic absorption spectroscopy by using the F-test and t-test. Neither F-value nor t-value have exceeded the critical values at 95% confidence level, confirming that there are no significant differences between the results obtained by both methods. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: ethanol fuel; solid paraffin-based carbon paste electrodes; organofunctionalized silica; copper ions; differential pulse stripping voltammetry